Analisis Preferensi Konsumen terhadap Keputusan Pembelian Bakso di Bakso Idola Mojosongo, Surakarta - Widyastuti, Rahayu Sri; Putri, Chiesa Albalia Rakhma; Sari, Devi Lintang; Rahadhini, Marjam Desma (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
This research is designed to identify the determine of consumer preferences on meatball products on purchasing decisions. The technique applied is quantitative descriptive method, with the population considered in this study being individuals who have experience enjoying Bakso Idola Mojosongo, Surakarta. The sampling technique used is accidental sampling with a total of 59 individuals. The instrument test uses the F test and T test formulas and hypothesis testing using the Chi-Square test. This study’s conclution reveal that there is an important correlation between consumer preferences and consumer purchasing decisions. This is validated by the outcomes of the Chi-Square test which shows the level of significance of each variable as follows: flavor (p= 0.001), texture (p= 0.000) and variance (p= 0.017).